2004
DOI: 10.1055/s-2004-827195
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic Alkyl Phloroglucinols fromProtorhus thouvenotii

Abstract: Two new cytotoxic alkylene phloroglucinols and one known compound were isolated through chromatographic separation from the methanolic extract of the dried fruits of Protorhus thouvenotii (Anacardiaceae). The compounds showed marginal in vitro cytotoxicity in the A2780 ovarian cancer cell line assay with an IC50 of 11 microg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Similar to 1, both the two double bonds in the side chain have the Z geometry according to the 13 C NMR chemical shifts of the bisallylic methylene carbon C-12" (δ C 25.6) and the two allylic carbons C-9" (δ C 27.2) and C-15" (δ C 27.2). 7,9 Actually, the NMR spectroscopic data of unit B in 3 were found to be in full agreement with those of thouvenol B 7 (7, Figure 1). As expected, subsequent analyses of the coupling constants, ROE correlations, and experimental ECD data ( Figure S4) revealed that 3 has the same absolute configuration as that of 2.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Similar to 1, both the two double bonds in the side chain have the Z geometry according to the 13 C NMR chemical shifts of the bisallylic methylene carbon C-12" (δ C 25.6) and the two allylic carbons C-9" (δ C 27.2) and C-15" (δ C 27.2). 7,9 Actually, the NMR spectroscopic data of unit B in 3 were found to be in full agreement with those of thouvenol B 7 (7, Figure 1). As expected, subsequent analyses of the coupling constants, ROE correlations, and experimental ECD data ( Figure S4) revealed that 3 has the same absolute configuration as that of 2.…”
supporting
confidence: 65%
“…9 This was supported by the upfield 13 C NMR resonances for the two bisallylic methylene carbons [δ C 25.6 (C-11") and 25.5 (C-14")] and the two allylic carbons [δ C 27.3 (C-8") and 20.5 (C-17")], which were in full agreement with those of reported resorcinols with two or more Z-configured double bonds in their alkenyl units. 7,9 These NMR data were superimposable on those of moniliferanone C (5) just isolated from the brown algae Cystophora subfarcinata. 6 The planar structure of unit B was then verified to be the same as 5 by further COSY and HMBC experiments ( Figure 2).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Phloroacetophenone derivatives such as thouvenol A and thouvenol B are reported to have cytotoxic activity against A2780 ovarian cancer cells. 30) In a recent report by Basabe et al, 2) the cytotoxic activities of various derivatives of phloroacetophenone in several cancer cell lines, HT-29, A549, HeLa, and HL-60 have been compared. Geranyl-phloroacetophenone was the most effective in inhibiting cell viability than farnesyl, oleyl, or stearyl derivatives.…”
Section: Discussionmentioning
confidence: 99%